Post Covid-19 water and waste water management to protect public health and geoenvironment. Issue 3 (1st October 2020) - Paleologos, Evan K; O'Kelly, Brendan C; Tang, Chao-Sheng; Cornell, Ken; Rodríguez-Chueca, Jorge; Abuel-Naga, Hossam; Koda, Eugeniusz; Farid, Arvin; Vaverková, Magdalena Daria; Kostarelos, Konstantinos; Goli, Venkata Siva Naga Sai; Guerra-Rodríguez, Sonia; et al.
Abstract : The coronavirus disease 2019 pandemic has posed severe threats to humans and the geoenvironment. The findings of severe acute respiratory syndrome coronavirus 2 (Sars-CoV-2) traces in waste water and the practice of disinfecting outdoor spaces in several cities in the world, which can result into the entry of disinfectants and their by-products into storm drainage systems and their subsequent discharge into rivers and coastal waters, raise the issue of environmental, ecological and public health effects. The aims of the current paper are to investigate the potential of water and waste water to operate as transmission routes for Sars-CoV-2 and the risks of this to public health and the geoenvironment. Additionally, several developing countries are characterised by low water-related disaster resilience and low household water security, with measures for protection of water resources and technologies for clean water and sanitation being substandard or not in place. To mitigate the impact of the pandemic in such cases, practical recommendations are provided herein. The paper calls for the enhancement of research into the migration mechanisms of viruses in various media, as well as in the formation of trihalomethanes and other disinfectant by-products in the geoenvironment, in order to develop robust solutions to combat the effects of the current and future pandemics.